Interannual variability of Indo-Pacific humpback dolphin (Sousa chinensis) habitats in the Eastern Pearl River Estuary, China - Shujie Wan; Guodong Li; Guodong Li; Guodong Li; Yutao Zhang; Yutao Zhang; Jing Cheng; Hang Yang (Frontiers in Marine Science)
Quantifying and analyzing the temporal and spatial variations of cetacean habitats is essential for establishing marine protected areas and preserving natural cetacean populations. Despite its importance, studies focusing on the interannual variability of cetacean habitats remain scarce. This study analyzed sighting records of Sousa chinensis and sea surface temperature (SST) data in the eastern Pearl River Estuary (PRE) from 2009 to 2022. Initially, the spatiotemporal variations in sighting effort and their correlation with SST were examined. Subsequently, the Suitability Index (SI) model was applied to calculate the distribution of S. chinensis habitats across different years and to assess interannual changes in habitat distribution in relation to climate change. The findings revealed that S. chinensis sightings were concentrated within a 227 km² area surrounding Lantau Island in the eastern PRE. The SST where sightings occurred ranged from 15.9°C to 29.8°C, with a strong positive correlation (r = 0.74, P<0.05) between sighting effort and SST. The SI model effectively identified habitat distribution patterns across years, highlighting a continuous decline in the area of suitable habitats (SI ≥ 0.6) from 2009 to 2022. The largest suitable habitat area was recorded in 2012 (a neutral year), while the smallest was observed in 2020 (a La Niña year). During ENSO events, suitable habitats exhibited a northward shift in average latitude. This study introduces novel methodologies for S. chinensis habitat research, supports the development of more effective monitoring strategies, and provides valuable insights for the establishment of marine protected areas.